Pengenalan Dasar Multimedia Bagi Pelayan Pemuda Gereja Pouk Ichthus BDP - Muhammad Rusli; Ridha Sefina Samosir; Cornelius Bagas Wicaksono; Joel Reinhard Bagenda (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
During a pandemic like this, it is tough for religious people to carry out worship comfortably and adequately, mainly when the crowd is limited to breaking the chain of the spread of the covid-19 virus. Therefore, my team and I are looking for a church that needs personnel in the multimedia field to help run online worship. This church is currently in need of personnel for the multimedia section. Pouk Ichthus BDP Church was founded in 1999 under PGI and Oikoumene. This church was established, the management was compiled and formed together through elections made by the congregation, such as the leading Pastor, Senior Pastor, chairman of the board and members of the assembly, all of them chosen by the church itself.